Avaliação histológica e funcional do enxerto de neotraqueia de coelho desenvolvido por bioengenharia - Evaristo, Thaiane Cristine [UNESP] (2015)
There is no standard treatment yet described in the literature for tracheal lesions whose length is more than 50% in adults and a third of the trachea in small children. Given the challenge of tracheal injuries treatment and the organ generation progress by tissue engineering techniques the interest in this area is growing considerably. Thereby this study aims to produce tracheal model for graft using tissue engineering techniques. Were performed five and 10 cycles of decellularization on donor rabbit‟s tracheae following the steps: freezing/defreezing without addition of any cryoprotectant; sonication in Ultrasonic cleaner (Unique model USC 1400®) with 40 Khz for 10 minutes; blue light-emitting diode (LED) irradiation with wavelength of 450nm ± 20nm along a dose of 90 J/cm2 at a total exposure of 60 minutes; addition of sodium deoxicholate detergent 4% during 48 hours under 180 rpm agitation in the C24 Incubator Shaker (New Brunswick Scientific). Meanwhile, expansion and characterization of mesenchymal stem cells of rabbits' receptors were performed with subsequent differentiation of these cells into chondrocytes and smooth muscle cells. Finally, it was realized the tracheal recellularization by the application of the mesenchymal stem cells, chondrocytes and smooth muscle cells from receptors rabbits in the outer face of the produced scaffolds for tracheal transplantation. After five repeated cycles of decellularization protocol used, it is still possible to observe respiratory epithelial cells and chondrocytes remaining in the tracheae of the donor rabbits. However, after 10 cycles of the same decellularization protocol the respiratory epithelial cells are completely removed and the tracheal cartilage chondrocytes are reduced. Animals that have been transplanted with five cycles decellularized tracheae had died after 10-12 days due to rejection by the presence of donor rabbit‟s epithelial cells. Animals that have been ...